Transformational Leadership dan Commitment to Change: Dimediasi oleh Readiness for Change Studi Pada Karyawan PT. Telkom Divisi Regional V Surabaya - Nurma Fitrianna; Tri Siwi Agustina (Forum Manajemen Indonesia (FMI), 2015)
Organizational change is a process whereby an organization change from the current state to the desired state to increase its effectiveness. These changes required the support of a leader, management, and all employees. The change will be successful if all of the organization's role in it. Someone who has a transformational leadership style will affect the readiness for change that will impact on the development and formation of commitment to change from employees. This study aimed to analyze the effect of transformational leadership toward commitment to change with readiness for change as a mediating variable. The variables used in this study are: transformational leadership, readiness for change, and commitment to change. This study uses a quantitative approach with survey method and supported by primary data from interviews and questionnaires. This study uses primary data from 70 employees, where the data is retrieved using a questionnaire distributed to permanent employees of PT. Telkom Divisi Regional V Surabaya. The analysis technique used is Partial Least Square (SmartPLS 3.0). The results showed that transformational leadership does not have a significant effect on the commitment to change, transformational leadership has a significant effect on the readiness for change, and readiness for change has a significant effect on the commitment to change. This means that the readiness for change proved to be a mediating variable and fully mediate between transformational leadership and commitment to change. Keyword: Transformational Leadership, Readiness for Change, and Commitment to Change